The Effect of Exercise Variations Dribble in Football Extracurricular Students of Riau Technological Vocational School Pekanbaru - Ahmad Yani (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2022)
This study aims to determine whether there is an effect of variations in practice on ball dribbling skills . in soccer extracurricular students at SMK Teknelogi Riau Pekanbaru, The type of research used is experimental. explained that research with an experimental approach is a study that seeks to find the effect of certain variables on other variables under tightly controlled conditions. Based on the calculation of the t value obtained tcount = 2.73. then compared with the value of the table t. From table t it is known that the value of ttable = 1.753, this means that tcount is greater than ttable. Thus, the research hypothesis Ho (zero/initial hypothesis) is rejected and the hypothesis Ha (alternative hypothesis) is accepted. Then the results show that there is a significant effect and has an increase in ability of 5.38%. Conclusion Based on the results of research and discussion, it can be concluded that there is an effect of variations in training on the dribbling soccer extracurricular students at SMK Teknologi Riau Pekanbaru by 5.38%. And the remaining 94.62% is influenced by other factors.